2013
DOI: 10.3855/jidc.2799
|View full text |Cite
|
Sign up to set email alerts
|

Antimycotic activity of Myrtus communis L. towards Candida spp. from clinical isolates

Abstract: This item has no abstact. Follow the link below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…The essential oils and extracts are gaining remarkable interest for their potential multipurpose use as an antioxidant (Amira et al, 2012;Serce et al, 2010), antibacterial (Appendino et al, 2006), antifungal (Cannas et al, 2013), and antiseptic (Cakir, 2004) agents. The effects of the essential oil of M. communis on the growth and survival of H. pylori were assessed and the results showed that the essential oil of this plant represented clear activity against clinical isolates of H. pylori (Deriu et al, 2007).…”
Section: Myrtus Communismentioning
confidence: 99%
“…The essential oils and extracts are gaining remarkable interest for their potential multipurpose use as an antioxidant (Amira et al, 2012;Serce et al, 2010), antibacterial (Appendino et al, 2006), antifungal (Cannas et al, 2013), and antiseptic (Cakir, 2004) agents. The effects of the essential oil of M. communis on the growth and survival of H. pylori were assessed and the results showed that the essential oil of this plant represented clear activity against clinical isolates of H. pylori (Deriu et al, 2007).…”
Section: Myrtus Communismentioning
confidence: 99%
“…More recently the pharmacological proprieties of its essential oil have been deeply explored. Antimicrobial properties (Deriu et al, 2007;Gündüz et al, 2009;Cannas et al, 2013), antihyperglycemic activities (Sepici et al, 2004;Onal et al, 2005), and antioxidant activity and fatty acid composition (Serce et al, 2010) have been also reported. A recent ethnobotanical study conducted by Leto et al (2013) showed effective medicinal use in both Italy (Sicily, Tuscany, and Sardinia) and Tunisia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the differences in the chemical composition of the EOs, they share some general properties, such as antiseptic, antibacterial, antifungal, and antioxidant activities [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%